Differences in risk factors for head and neck cancer among men and women in Nepal: A case-control study. (February 2023) - Shrestha, Gambhir; Chang, Chun-Pin; Pun, Chin Bahadur; Gautam, Dej Kumar; Siwakoti, Bhola; Sapkota, Amir; Hashibe, Mia
Abstract: Background: Head and neck cancer (HNC) is a major cause of cancer morbidity and mortality in Nepal. The study aims to investigate differences in risk factors for head and neck cancer by sex in Nepal. Methods: A hospital-based case-control study was conducted at the B.P. Koirala Memorial Cancer Hospital in Nepal from 2016 to 2018. A semi-structured questionnaire consisting of socio-demographic characteristics, dietary habits, reproductive factors, household air pollution, tobacco use (smoking and chewing), alcohol consumption, and second-hand smoking was used to collect the data. Odds ratios (OR) and 95 % confidence intervals (CI) were estimated using unconditional logistic regression adjusting for potential confounders. Results: A total of 549 HNC cases (438 men and 111 women) and 601 age-matched healthy controls (479 men and 122 women) were recruited in this study. An increased risk of HNC for low education level and family income were observed among men (adjusted odds ratio (AOR) for 3rd grade and less= 1.58, 95 % CI= 1.14–2.18; AOR for family monthly income < 5000 Rupees = 1.64, 95 % CI 1.20–2.24). The AORs among women were higher than the men for known risk factors (AOR for smoking 1.34 (95 % CI 0.96–1.86) for men, 2.94 (95 % CI 1.31–6.69) for women; AOR for tobacco chewing 1.76 (95 % CI 1.27–2.46) for men, 10.22 (95 % CI 4.53–23.03) for women). Conclusion: Our results point to an effect modification by sex for HNC risk factors with high AORs observed among women. Highlights: Effect modification by sex for HNC risk factors was observed. The risk of HNC for tobacco smoking was almost double in women compared to men. Men had higher prevalence for known risk factors of HNC compared to women.